Destructive leadership and management hypocrisy : advances in theory and practice - Camgöz, Selin Metin; Ekmekci, Özge Tayfur (Emerald Publishing Limited, 2021)
When evaluating leadership, bad events 'have more impact than good ones, and bad information is processed more thoroughly than good'. Destructive Leadership and Management Hypocrisy: Advances in Theory and Practice provides detailed insights into conceptualizations of destructive leadership, instruments of measurement in this area, and reviews studies about the concept's antecedents and consequences. Divided into functional sections exploring definitional issues and conceptual clarifications in destructive leadership, a range of issues are covered including:;Holistic definitions of destructive leadership ;Dispositional characteristics of destructive leaders, and their environment ;Pseudo transformational, laissez-faire, and unethical leadership ;Leader hypocrisy, integrity, and its consequences ;Destructive leadership from a cross-cultural perspective ;Outcomes of destructive leadership and leader hypocrisy Readers will gain a deeper understanding of the implications of destructive leadership and find value in the immediate application of these warnings and lessons to their own careers and organizations.